Mouse embryonic stem cell-derived blood–brain barrier model: applicability to studying antibody triggered receptor mediated transcytosis - Jezierski, Anna; Huang, Jez; Haqqani, Arsalan S.; Haukenfrers, Julie; Liu, Ziying; Baumann, Ewa; Sodja, Caroline; Charlebois, Claudie; Delaney, Christie E.; Star, Alexandra T.; Liu, Qing; Stanimirovic, Danica B. (Université d'Ottawa | University of Ottawa, 2023)
Abstract Blood brain barrier (BBB) models in vitro are an important tool to aid in the pre-clinical evaluation and selection of BBB-crossing therapeutics. Stem cell derived BBB models have recently demonstrated a substantial advantage over primary and immortalized brain endothelial cells (BECs) for BBB modeling. Coupled with recent discoveries highlighting significant species differences in the expression and function of key BBB transporters, the field is in need of robust, species-specific BBB models for improved translational predictability. We have developed a mouse BBB model, composed of mouse embryonic stem cell (mESC-D3)-derived brain endothelial-like cells (mBECs), employing a directed monolayer differentiation strategy. Although the mBECs showed a mixed endothelial-epithelial phenotype, they exhibited high transendothelial electrical resistance, inducible by retinoic acid treatment up to 400 Ω cm2. This tight cell barrier resulted in restricted sodium fluorescein permeability (1.7 × 10–5 cm/min), significantly lower than that of bEnd.3 cells (1.02 × 10–3 cm/min) and comparable to human induced pluripotent stem cell (iPSC)-derived BECs (2.0 × 10–5 cm/min). The mBECs expressed tight junction proteins, polarized and functional P-gp efflux transporter and receptor mediated transcytosis (RMT) receptors; collectively important criteria for studying barrier regulation and drug delivery applications in the CNS. In this study, we compared transport of a panel of antibodies binding species selective or cross-reactive epitopes on BBB RMT receptors in both the mBEC and human iPSC-derived BEC model, to demonstrate discrimination of species-specific BBB transport mechanisms.